Expanded pilot newborn screening for lysosomal disorders: First results from Turkey - Okur, Ilyas; Oktem, Murat R.; Inci, Asli; Ozbek, Mehmet N.; Akgun, Abdurrahman; Yildirimd, Gonca Kilic; Tumera, Leyla (Academic Press Inc Elsevier Science, 2025)
[Abstract Not Available]
21st Annual World Symposium -- FEB 03-07, 2025 -- San Deigo, CA